The Causal Effects of Lipid Profiles on Sleep Apnea - Tang, Hongyi; Zhou, Qing; Zheng, Fu; Wu, Tong; Tang, Yi-Da; Jiang, Jiuhui (Frontiers in Nutrition, 2022)
Introduction Observational studies have suggested that lipid profiles were associated with risk of sleep apnea (SA). However, the specific lipid types and whether this relationship has a causal effect are uncertain. This study conducted two-sample Mendelian randomization (MR) and multivariable Mendelian randomization (MVMR) to investigate the potential causal relationship between lipid profiles and risk of SA. Materials and Methods We used the largest genome-wide association study (GWAS) on European participants on the UK Biobank. After a rigorous single nucleotide polymorphism screening process to remove confounding effects, we performed MR and MVMR to explore the causal relationship between lipid profiles and SA risk. Results Both MR and MVMR showed causal effects of increased triglyceride on SA risk [MR: per 10 units, odds ratio (OR): 1.0156; 95% CI: 1.0057–1.0257; P value = 0.002; MVMR: per 10 units, OR: 1.0229; 95% CI: 1.0051–1.0411; P value = 0.011]. The sensitivity analysis including Cochran’s Q test, MR-Egger intercept, and MR pleiotropy residual sum and outlier (MR-PRESSO) test indicated that our findings were robust. The causal effects of triglyceride on SA did not change after adjusting for potential confounders (obesity, age, sex, and airway obstruction). Conclusion Genetically increased triglyceride levels have independent causal effects on risk of sleep apnea without the confounding effects of obesity, suggesting that lowering triglyceride concentrations may help to reduce the risk of sleep apnea.